Malaysia hungers for more Professional Engineers - Wan Sharuzi, Wan Harun (2020)
The journey of an engineer begins from obtaining a scroll of an engineering degree till becoming a professional practitioner in their engineering field or better known as Professional Engineer (PE). Becoming a Professional Engineer can be considered as the highest achievement for all engineering graduates in any area. The recognition as a Professional Engineer will provide a sense of triumph to anyone passionate about their engineering profession. Professional Engineer will only deliver the tasks based on their most exceptional engineering knowledge, accurate problem analysis, optimum solution to the problem, comprehensive investigation and analysis, utilisation of best available tools, environmental and sustainability safeguard, a high priority of public safety, and sound judgement in project management through ethical practices. In Malaysia, there are various sectors for our engineers to serve including consultation, research & development, construction, building services, maintenance, manufacturing, plantation, aviation, maritime, sales, and oil & gas industry, as well as institutions of higher learning like universities and colleges as a lecturer or a teaching engineer.